2015
DOI: 10.1080/14649365.2015.1020335
|View full text |Cite
|
Sign up to set email alerts
|

On the spatiality of the academic job market in critical human geography

Abstract: This essay uses a geographical vocabulary to describe the process of looking for and obtaining academic employment in critical human geography since the onset of the global recession. The first goal of this paper is to document a transformative moment in the history of geography by narrating stories of the job hunt. The second goal of the paper is to map the liminality, precarity, and contradictions of the contemporary job search. The final goal is to reflect on how the academic job search affects our approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Just as importantly, through these practices and performances these places are made and remade. While work on the spatialities of research work and identities is thus far limited (though see Gillen ), we draw here on McAlpine and Mitra's () suggestion of the important role played by institutional spaces in fostering research work and identification and Hopwood and Paulson's () elaboration of the spatial constitution of PhD emotions. In particular, we are alert to the interplay of materials, meanings and identities in the spaces of the PhD.…”
Section: Space Research Work and Researcher Identificationsmentioning
confidence: 99%
“…Just as importantly, through these practices and performances these places are made and remade. While work on the spatialities of research work and identities is thus far limited (though see Gillen ), we draw here on McAlpine and Mitra's () suggestion of the important role played by institutional spaces in fostering research work and identification and Hopwood and Paulson's () elaboration of the spatial constitution of PhD emotions. In particular, we are alert to the interplay of materials, meanings and identities in the spaces of the PhD.…”
Section: Space Research Work and Researcher Identificationsmentioning
confidence: 99%
“…First, the neoliberalisation of academic job market has been marginalising social science research through casualising academic labour (McAlpine, 2010). In particular, the ‘unknowingness’ of job security and uncertainty of work-life balance have been affecting early career critical human geographers, shifting their career aspirations (Gillen, 2015). This problem is irreducible to academic tenure and Geography departments in Western research institutions, and is beyond our focus on Geography.…”
Section: Is Geography (Becoming) a ‘Broken Bottle’?mentioning
confidence: 99%
“…Another student saw his inability to move where work was available (Gillen, ; Hammett, ) as an important barrier to pursuing a post‐PhD career in academia, writing: ‘I'd like to be able to remain in [my local] … area to be near family and friends … I feel this limits my future job prospects’. Others felt they were neither willing nor able to meet the high standards required to obtain work in academia:
I worry that I won't be able to find work—I feel like … I will be competing with [others who] are probably more willing and capable of doing things that I am not (for example, moving long distances from home, working 60 hours a week, publishing many articles each year).
…”
Section: Anticipating and Preparing For Post‐phd Careersmentioning
confidence: 99%
“…In an analysis of early career academics, Solem and Foote (, p.889) found that many new faculty members struggled to maintain healthy personal and family lives. The perspectives of the aforementioned participants indicate that this struggle begins before graduation with practices developed during the PhD candidature effectively training students into problematic work patterns that they will take with them into their post‐PhD work (Gillen, ). Not only are these practices detrimental at the individual level but also they become particularly nefarious when, collectively, they work against wider agendas of pursuing greater diversity in graduate student and faculty populations.…”
Section: Anticipating and Preparing For Post‐phd Careersmentioning
confidence: 99%
See 1 more Smart Citation